Pembinaan Guru Dengan Pendekatan Supervisi Klinis - Maunah, Binti (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
This article offers clinical supervision for teachers in order to tackle some problems while teaching and to anticipate some possible problems that may appear. This professional assistance is done by a supervisor to teachers in order to fill in the gap between the real teaching behaviors and the ideal teaching behaviors. This can be done individually and in group. The cycles of the clinical supervision are of three stages: early meeting, classroom observation, and feedback provision.